Short report: Experience of black patients in a critical care unit in a hospital in Pietermaritzburg - R. M. S. Gwala (AOSIS, 1993)
At the time of this study, the researcher was working as the matron in charge of the Critical Care Units (CCU) of a large hospital in Edendale, Pietermaritzburg. She was aware of an abundance of literature on the C.C.U. environment and its effect on both staff and patients in overseas work but found nothing documenting reactions of South African black patients to their C.C.U. experience.